PELATIHAN PEMBUATAN SURAT LAMARAN KERJA MENGGUNAKAN MICROSOFT WORD PADA PKBM DHARMA PUTRA MANDIRI - Rizky Pradana; Dwi Achadiani (Universitas Islam Indonesia, 2020)
Dedication to society is obligator by lecturers, because carried on tridharma college. The implementation of the PKM in this time involved counterpart of Community learning activity centers (PKBM) Dharma Putra Mandiri. The Probelem in this PKBM are lack of lab for practicing computer, while in this era computer is a part for doing some works. To solve that problem, team of PKM give some solution, the solution for this problem is give the training of basic computer which utilize microsoft word application for the students in PKBM Dharma Putra Mandiri, this training hopefully the stidents get experience in operating computer. To increase the kuality except do the basics of microsoft word, in this training giving case to create CV, wich utilize this application. Besides that, in this training, the participan will get certiicate competency ich can be used as attachment between certificate degree. Based on this training, every participant can increase the kuality in ICT, especially in CV creating with microsoft word application. Result in this PKM sparate in two category, the catogory are assesment for participant and PKM team. The assesment to participant get averages of post test in 51%, with maimum value is 10 in 0-10 of range, and the best result of assignment for the PKM team is 71% in infrastructure.